Influence of SCD and FABP3 genetic markers on carcass traits and meat quality in Aberdeen Angus bulls - Sena Ardicli; Nursen Senturk; Tugce Necla Selvi; Sena Yonga; Rumeysa Celik; Beyza Karalar; Aleyna Ozdeniz; Madina Aliyeva; Havvanur Aydin; Ozgur Toprak Ay; Ozge Ardicli; Muhammed Emin Sari; et al. (Revista Brasileira de Zootecnia)
ABSTRACT This study evaluated the association of stearoyl-CoA desaturase (SCD) and fatty acid-binding protein 3 (FABP3) gene polymorphisms with carcass and meat quality traits in Aberdeen Angus bulls. Two hundred seventy-four Angus bulls were genotyped using PCR-RFLP and Sanger sequencing. Next, the association of SCD and FABP3 genetic variants with traits such as live weight, average daily weight gain, carcass weight (both hot and cold), dressing percentage, carcass length, back fat thickness, carcass color score, pH, and marbling score was analyzed. Significant differences were observed in average daily weight gain among different FABP3 genotypes, with the GG genotype showing the highest gains (P<0.01). Furthermore, novel associations between the SCD × FABP3 interaction and key traits were identified, including dressing percentage and carcass pH. Notably, an epistatic pattern through this genotypic interaction was demonstrated, which may significantly influence postmortem pH decline in beef cattle. The results suggest a notable impact of the FABP3 rs210042291 gene on growth rates. These findings highlight the complexity of genetic influences on meat quality traits.